Multiplatform metabolomic analysis of the R6/2 mouse model of Huntington's disease. Issue 10 (14th September 2021) - Hashimoto, Masayo; Watanabe, Kenichi; Miyoshi, Kan; Koyanagi, Yukako; Tadano, Jun; Miyawaki, Izuru
Abstract : Huntington's disease (HD) is a progressive, neurodegenerative disease characterized by motor, cognitive, and psychiatric symptoms. To investigate the metabolic alterations that occur in HD, here we examined plasma and whole‐brain metabolomic profiles of the R6/2 mouse model of HD. Plasma and brain metabolomic analyses were conducted using capillary electrophoresis–mass spectrometry (CE‐MS). In addition, liquid chromatography–mass spectrometry (LC‐MS) was also applied to plasma metabolomic analyses, to cover the broad range of metabolites with various physical and chemical properties. Various metabolic alterations were identified in R6/2 mice. We report for the first time the perturbation of histidine metabolism in the brain of R6/2 mice, which was signaled by decreases in neuroprotective dipeptides and histamine metabolites, indicative of neurodegeneration and an altered histaminergic system. Other differential metabolites were related to arginine metabolism and cysteine and methionine metabolism, suggesting upregulation of the urea cycle, perturbation of energy homeostasis, and an increase in oxidative stress. In addition, remarkable changes in specific lipid classes are indicative of dysregulation of lipid metabolism. These findings provide a deeper insight into the metabolic alterations that occur in HD and provide a foundation for the future development of HD therapeutics. Abstract : Multiplatform metabolomic analysis revealed several perturbed metabolic pathways in the R6/2 mouse model of Huntington's disease. Altered histidine metabolism in the brain indicates neurodegenerative status and an altered histaminergic system. Changes in the metabolism of arginine, cysteine, and methionine, and various lipid species were also highlighted. These findings add deeper insights into the metabolic alterations in Huntington's disease.